Profil Nutrisi Kulit Buah Kakao yang Difermentasi dengan Fermentor Berbeda - Bulkaini Bulkaini; Muhamad Ashari; Tarmizi Tarmizi; I Wayan Karda (Jurnal Ilmu Dan Teknologi Peternakan Indonesia (JITPI) Indonesian Journal of Animal Science and Technology), 2015)
In the experiment reported in this paper, fresh cocoa pod husk was ensiled in a concrete silo with or without starter for 9 days in the Faculty of Animal Science, Mataram University. Three experimental treatments were tested in three replications which include fresh cocoa pod husk ensiled with 1. 5% rice bran, 0.5% fertilizer grade urea, with no starter added (T1), as for T1 but with addition of cows strained rumen fluid (T2) and as for T!, but with added commercial starter bioplus (T3). The treatment process was done in three periods of 9 days each and samples were taken three times accordingly for proximate analyses including dry matter, ash, ether extract, crude protein, crude fibre, and nitrogen free extract contents of the resulting silages. The experiment was arranged in a Completely Randomized Design and aimed at supplying direct feed requirements for a feeding trial using cattle which was lasted for 6 weeks. The result showed that no significant difference could be detected in the nutritional values among the ensiled products in term of total ash, ether extract, crude fibers, crude protein, NDF/ADF contents as well as organic matter digestibility. Dry matter digestibility of T3 was significantly higher (p<0.05) than T1, but did not significantly differ from T2. Moreover, T2 was not also significantly different from T1. Although P3 had the highest dry matter digestibility compared to the other treatments, no significant improvement in the voluntary feed intake, live body weight change and feed conversion efficiency has been observed in a feeding trial with young Bali cattle (approximately BW 200 kg) fed these three ensiled products supplemented with 1% BW of commercial concentrate feed given fresh aerial parts of corn stover.